MAIN STAGES OF THE CONCERT MASTER’S WORK IN THE CONDITIONS OF DISTANCE LEARNING IN THE CLASSES OF "VOICE" - Мітєва, А.М. (SWorldJournal, 2022)
The article reveals the main stages of the accompanist’s workin the classes "Voice Production", the peculiarities of the formation of creative potential of the individual with the help of innovative technologies